The C-terminus of non-structural protein 1 (NS1) in H5N8 clade 2.3.4.4 avian influenza virus affects virus fitness in human cells and virulence in mice. Issue 1 (1st January 2021) - Blaurock, Claudia; Blohm, Ulrike; Luttermann, Christine; Holzerland, Julia; Scheibner, David; Schäfer, Alexander; Groseth, Allison; Mettenleiter, Thomas C.; Abdelwhab, Elsayed M.
ABSTRACT: Avian influenza viruses (AIV) H5N8 clade 2.3.4.4 pose a public health threat but the viral factors relevant for its potential adaptation to mammals are largely unknown. The non-structural protein 1 (NS1) of influenza viruses is an essential interferon antagonist. It commonly consists of 230 amino acids, but variations in the disordered C-terminus resulted in truncation or extension of NS1 with a possible impact on virus fitness in mammals. Here, we analysed NS1 sequences from 1902 to 2020 representing human influenza viruses (hIAV) as well as AIV in birds, humans and other mammals and with an emphasis on the panzootic AIV subtype H5N8 clade 2.3.4.4A (H5N8-A) from 2013 to 2015 and clade 2.3.4.4B (H5N8-B) since 2016. We found a high degree of prevalence for short NS1 sequences among hIAV, zoonotic AIV and H5N8-B, while AIV and H5N8-A had longer NS1 sequences. We assessed the fitness of recombinant H5N8-A and H5N8-B viruses carrying NS1 proteins with different lengths in human cells and in mice. H5N8-B with a short NS1, similar to hIAV or AIV from a human or other mammal-origins, was more efficient at blocking apoptosis and interferon-induction without a significant impact on virus replication in human cells. In mice, shortening of the NS1 of H5N8-A increased virus virulence, while the extension of NS1 of H5N8-B reduced virus virulence and replication. Taken together, we have described the biological impact of variation in the NS1 C-terminus in hIAV and AIV and shown that this affects virus fitness in vitro and in vivo .